Providers' Perceptions and Training Needs for Counseling Adolescents Undergoing Voluntary Medical Male Circumcision. (3rd April 2018) - Tobian, Aaron A R; Dam, Kim H; Van Lith, Lynn M; Hatzold, Karin; Marcell, Arik V; Mavhu, Webster; Kahabuka, Catherine; Mahlasela, Lusanda; Patel, Eshan U; Njeuhmeli, Emmanuel; Seifert Ahanda, Kim; Ncube, Getrude; et al.
Abstract: Background: The majority of individuals who seek voluntary medical male circumcision (VMMC) services in sub-Saharan Africa are adolescents (ages 10–19 years). However, adolescents who obtain VMMC services report receiving little information on human immunodeficiency virus (HIV) prevention and care. In this study, we assessed the perceptions of VMMC facility managers and providers about current training content and their perspectives on age-appropriate adolescent counseling. Methods: Semistructured in-depth interviews were conducted with 33 VMMC providers in Tanzania (n = 12), South Africa (n = 9), and Zimbabwe (n = 12) and with 4 key informant facility managers in each country (total 12). Two coders independently coded the data thematically using a 2-step process and Atlas.ti qualitative coding software. Results: Providers and facility managers discussed limitations with current VMMC training, noting the need for adolescent-specific guidelines and counseling skills. Providers expressed hesitation in communicating complete sexual health information—including HIV testing, HIV prevention, proper condom usage, the importance of knowing a partner's HIV status, and abstinence from sex or masturbation during wound healing—with younger males (aged <15 years) and/or those assumed to be sexually inexperienced. Many providers revealed that they did not assess adolescent clients' sexual experience and deemed sexual topics to be irrelevant or inappropriate. Providers preferred counseling younger adolescents with their parents or guardians present, typically focusing primarily on wound care and procedural information. Conclusions: Lack of training for working with adolescents influences the type of information communicated. Preconceptions hinder counseling that supports comprehensive HIV preventive behaviors and complete wound care information, particularly for younger adolescents.